2009
DOI: 10.1007/s10534-008-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Di-iron proteins of the Ric family are involved in iron–sulfur cluster repair

Abstract: A key element in eukaryotic immune defenses against invading microbes is the production of reactive oxygen and nitrogen species. One of the main targets of these species are the iron-sulfur clusters, which are essential prosthetic groups that confer to proteins the ability to perform crucial roles in biological processes. Microbes have developed sophisticated systems to eliminate nitrosative and oxidative species and promote the repair of the damages inflicted. The Ric (Repair of Iron Centers) proteins constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Twelve highly conserved amino acid residues were selected, based on the amino acid sequence alignment of the so far available RIC proteins [4,11] and on the homology modelling herein described. E. coli RIC mutated proteins were constructed by sitedirected mutagenesis (Supplementary Material).…”
Section: Site-directed Mutagenesis Of E Coli Ric and Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve highly conserved amino acid residues were selected, based on the amino acid sequence alignment of the so far available RIC proteins [4,11] and on the homology modelling herein described. E. coli RIC mutated proteins were constructed by sitedirected mutagenesis (Supplementary Material).…”
Section: Site-directed Mutagenesis Of E Coli Ric and Protein Productionmentioning
confidence: 99%
“…Interestingly, two orthologues are also found in the eukaryote Trichomonas vaginalis, an important human pathogenic protozoan [4]. RIC proteins exhibit conserved residues and, in particular, amino acids H84, H105, H129, E133, H160, and H204 (numbering referring to E. coli RIC) are highly conserved and predicted to be located in alpha-helix regions [4,11]. In this work, homology-based modelling [12] was used to generate the tridimensional structure of the E. RIC, and retrieve residues that are the putative ligands of the diiron centre or closely located to it.…”
Section: Introductionmentioning
confidence: 99%
“…Homologues of E. coli RIC have a widespread distribution in nature, including in Eukarya [8], [9] and their importance in the repair of damaged Fe-S centers was also shown for the human pathogens Staphylococcus aureus and Neisseria gonorrhea [8]. In vivo assays revealed that RIC contributes to the survival of Haemophilus influenza in activated macrophages [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since RIC was shown to be involved in repair of Fe-S clusters damaged by both stresses, we previously proposed that RIC may act as an iron donor [9]. In this work, the ability of RIC to donate iron for the assembly of an Fe-S center into the apo-form of spinach ferredoxin and of the E. coli scaffold IscU was analyzed by UV-visible, EPR and resonance Raman spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Since [Fe-S] proteins are targets for inactivation by NO (Hyduke et al, 2007;Ren et al, 2008), upregulation of an [Fe-S] repair system by NO makes good physiological sense. Indeed, the NsrR-regulated ytfE gene encodes a protein with a role in [Fe-S] cluster repair (Justino et al, 2009).…”
Section: Nsrr Regulates Expression Of the Suf Iron -Sulfur Cluster Rementioning
confidence: 99%